2016
DOI: 10.1177/1077546315626323
|View full text |Cite
|
Sign up to set email alerts
|

Combination of map-based and adaptive feedforward control algorithms for active engine mounts

Abstract: Active engine mounts significantly contribute to ensure the comfort in vehicles with emission-reducing engine technologies, e.g., cylinder-on-demand (COD), downsizing or turbochargers. To control active engine mounts, either adaptive or non-adaptive feedforward control is commonly employed. Since both approaches have previously been treated separately, this study proposes methods to connect them in terms of multiple-input-multiple-output Newton/FxLMS adaptive filters with self-trained, grid-based look-up table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…According to the references [35][36][37], it is assumed that the maximum value of the relative displacement between the engine and the sprung mass is 0.4mm, and the free stroke of the MA in section 5.1 is ±50μm, so take = 8. The other part is the model of the two-degree-of-freedom active mounting system, which is established using equations (14), (24), (25) and (26) based on the derived x-LMS algorithm with state feedback and Sage-Husa Kalman filter. The parameters of the model of the two-degree-of-freedom active mounting system are shown in Table 2.…”
Section: Simulation Of Two-degree-of-freedom Active Mounting Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the references [35][36][37], it is assumed that the maximum value of the relative displacement between the engine and the sprung mass is 0.4mm, and the free stroke of the MA in section 5.1 is ±50μm, so take = 8. The other part is the model of the two-degree-of-freedom active mounting system, which is established using equations (14), (24), (25) and (26) based on the derived x-LMS algorithm with state feedback and Sage-Husa Kalman filter. The parameters of the model of the two-degree-of-freedom active mounting system are shown in Table 2.…”
Section: Simulation Of Two-degree-of-freedom Active Mounting Systemmentioning
confidence: 99%
“…Active mounts can achieve better vibration isolation and relative displacement control performance in a broader frequency bandwidth via active force [3][4][5]. In the research of active mounting systems, the actuators and control methods that directly affect system performance have received extensive attention [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…To meet the requirements of low emissions and low fuel consumption, downsizing, on-demand cylinders (COD), turbochargers, and active fuel management are applied in vehicles [1][2][3][4][5], which results in changes in the engine vibration excitation level and dominant engine order shown in Figures 1(a) and 1(b). Attenuation of the vibration from the engine is the most challenging and disruptive vibrational problem.…”
Section: Introductionmentioning
confidence: 99%
“…Buttelmann et al [13] identified the Bode plot of the secondary path between the active absorber and the disturbance sensor on the chassis side of the engine mount. Hausberg et al [14] identified the secondary path between the active engine mount and the accelerometer located on the chassis side of the engine mount for the feedforward control. Fakhari et al [15,16] identified the transfer function of the secondary path between the input current of the ARM and the transmitted force on the engine side by curve fitting, which is expressed by the poles and zeros of the transfer function.…”
Section: Introductionmentioning
confidence: 99%